The effect of beta 2-adrenoceptor stimulation and blockade of L-type calcium channels on in vivo Na+/H+ antiporter activity in rat skeletal muscle. - Syme, P; Brunotte, F; Green, Y; Aronson, J; Radda, G (1991)
We have studied the in vivo response of the Na+/H+ antiporter in skeletal muscle to beta 2-adrenoceptor stimulation with isoprenaline and the effect of blocking L-type calcium channels with nifedipine. Na+/H+ antiporter activity in skeletal muscle in vivo increased after beta 2-adrenoceptor stimulation with isoprenaline; nifedipine attenuated that effect. This suggests that opening of L-type calcium channels is necessary for full activation of the Na+/H+ antiporter in skeletal muscle. Bleeding also increased Na/H+ antiporter activity, which we believe could be explained by an increase in sympathetic nervous system activity as a result of hypotension. This may be one of the mechanisms by which animals under stress prepare their skeletal muscle for exercise as part of the 'fright and flight' reaction.